2009
DOI: 10.4049/jimmunol.0900389
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles of B and T Lymphocyte Attenuator in NKT Cell-Mediated Experimental Hepatitis

Abstract: Although B and T lymphocyte attenuator (BTLA) was originally identified as an inhibitory coreceptor selectively expressed on Th1 cells and B cells, recent studies have revealed that BTLA is expressed on a variety of cells, including macrophages, dendritic cells, and NK cells, and modulates their functions. However, the role of BTLA in the regulation of NKT cell function remains unknown. In this study, we found that BTLA was expressed on NKT cells at the levels similar to those on T cells and that BTLA-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…[23][24][25] The humoral immune response and propensity to develop autoimmune diseases are enhanced not only in BTLA-deficient mice 23,35 but also in HVEM-deficient mice. 48 The latter strengthens the predominant in vivo function of HVEM as an inhibitory ligand rather than a costimulatory ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] The humoral immune response and propensity to develop autoimmune diseases are enhanced not only in BTLA-deficient mice 23,35 but also in HVEM-deficient mice. 48 The latter strengthens the predominant in vivo function of HVEM as an inhibitory ligand rather than a costimulatory ligand.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 The experimental evidence of the role of the BTLA/ HVEM pathway in humoral immunity comes from the analysis of the phenotype of BTLA-deficient mice, which revealed defects in the regulation of this branch of immunity with implications in the development of autoimmune diseases. [23][24][25] As the HVEM receptor is the unique known partner of BTLA and both molecules are expressed on T and B cells, we postulated that the HVEM/BTLA signalling pathway may participate in providing CD4 help to B cells for the production of donorspecific antibodies. 20 With this notion in mind, we set up an experimental approach to elucidate the role of this interaction in the context of the humoral immune response during the acute phase of graft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…B and T lymphocyte attenuator (BTLA; CD272) is the third inhibitory coreceptor, which has been identified as an inhibitory coreceptor expressed on CD4 + T cells and B cells with similarities to CTLA-4 and PD-1 (9 ) mice have revealed that BTLA plays inhibitory roles in a variety of disease models, including experimental autoimmune encephalomyelitis (9), partially MHC-mismatched cardiac allograft (12), experimental colitis (13), and experimental hepatitis (14). We have also shown that the deficiency of BTLA spontaneously causes the breakdown of self-tolerance, resulting in the development of an autoimmune hepatitis-like disease and lymphocytic infiltration in multiple organs in aged mice (15).…”
Section: B and T Lymphocyte Attenuator Inhibits Lps-inducedmentioning
confidence: 99%
“…Conversely, the rs2705535 TT genotype increased rectal cancer risk 84.1 % when compared to the CC + CT genotype. Additionally, the risk of rectal cancer in carriers of the TT genotype is 1.819-fold greater than that of the CC ( abe et al 2003b;Hurchla et al 2005;Murphy et al 2006;Iwata et al 2010). The inhibitory signal of BTLA appears to be mediated by the recruitment of SHP-1 and SHP-2 to two immunoreceptor tyrosine inhibitory motifs (ITIMs) in the cytoplasmic region of BTLA (Watanabe et al 2003a).…”
Section: Discussionmentioning
confidence: 96%